Zonisamide Induces Crystalluria without Urinary pH Changes in Children and Young Adults. (19th September 2013) - Go, Tohshin
Abstract : Purpose . Adjunctive zonisamide therapy was demonstrated to be beneficial for multiple-disabled patients with refractory childhood-onset epilepsy. Zonisamide is well tolerated, but urolithiasis and calcium sludge in the bladder were sometimes described in patients treated with antiepileptic drug polytherapy including zonisamide. In previous studies, alkaline urine and crystalluria were shown to be risk factors for urolithiasis. Therefore, the effects of zonisamide addition and withdrawal on the urinary pH and crystalluria were investigated in patients treated with antiepileptic drug polytherapy to clarify the cause of urolithiasis induced by zonisamide. Methods . The urinary pH and the degree of crystalluria were retrospectively studied in epilepsy patients one month after the addition or withdrawal of zonisamide as part of their antiepileptic drug treatment regimen over the previous three years. Results . A total of 27 zonisamide-on patients and 16 zonisamide-off patients were enrolled in the study. The urinary pH did not change after the addition or withdrawal of zonisamide. However, the degree of crystalluria significantly increased after the addition (P < 0.001 ) of zonisamide and decreased after its withdrawal (P < 0.01 ). Conclusions . Zonisamide induces crystalluria without alkalinization of the urine. Crystalluria should be carefully monitored in patients treated with zonisamide to prevent urolithiasis.